Design of Robust Decentralized Deregulated Fuzzy LFC-DR Model for an Interconnected Power System - Srividya Devi, P.; Vijaya Santhi, R. (International Journal of Engineering and Technology, 2019)
From the past few years Demand Response (DR) is playing a prominent role in Load Frequency Control (LFC) This leads to focus on LFC-DR model. For aggregating the small scale controllable loads Demand Response Load Frequency Control(LFC-DR) is widely used for distant measurements and control. Communication delay latency also plays a vital role in LFC-DR model. This paper investigates the control design for the Deregulated LFC-DR model. Communication delay latencies are linearized using rational approximations. Here Padé approximation with equal degree is employed. A robust Fuzzified Proportional Integral Derivative (Fuzzy-PID) controller is designed to deal with the latencies and load perturbations with DR loop. Case studies based on the two-area deregulated LFC-DR model is demonstrated. The efficacy of the proposed controller is observed by comparing with conventional controller under Deregulated LFC(DLFC) and Deregulated LFC-DR with different control.
Keywords: Demand Response; Fuzzy logic controller; Deregulated Environment.; Load frequency control; Latency; PadÃ© Approximation